2011
DOI: 10.3109/08923973.2011.574704
|View full text |Cite
|
Sign up to set email alerts
|

WNT/β-catenin pathway is modulated in asthma patients and LPS-stimulated RAW264.7 macrophage cell line

Abstract: In the present study, we investigated the possibility that the WNT/β-catenin pathway plays a role in inflammatory responses both in an human inflammatory condition and in an in vitro inflammation model. First, we analyzed gene expression patterns of the peripheral blood cells from asthma patients compared with those from normal subjects using microarray analyses. We found that intracellular signaling molecules of the WNT/β-catenin pathway were significantly changed in asthma patients compared with the levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 70 publications
2
37
0
Order By: Relevance
“…19,20 Here, we observed that IL-6 in the BAL was markedly reduced after the administration of Wnt3a in LM-challenged lungs ( Figure 5D), and this reduction was due to attenuated IL-6 mRNA synthesis by Wnt3a ( Figure 5E). However, mRNA expression and the BAL level of TNFa showed no significant difference between Wnt3a-treated and control mice upon LM challenge (supplemental Figure 4C-D).…”
Section: An Antibody Capable Of Neutralizing Dkk1 Attenuates Neutrophmentioning
confidence: 74%
See 3 more Smart Citations
“…19,20 Here, we observed that IL-6 in the BAL was markedly reduced after the administration of Wnt3a in LM-challenged lungs ( Figure 5D), and this reduction was due to attenuated IL-6 mRNA synthesis by Wnt3a ( Figure 5E). However, mRNA expression and the BAL level of TNFa showed no significant difference between Wnt3a-treated and control mice upon LM challenge (supplemental Figure 4C-D).…”
Section: An Antibody Capable Of Neutralizing Dkk1 Attenuates Neutrophmentioning
confidence: 74%
“…19 Knockdown of b-catenin in macrophages increases LPSinduced IL-6 expression. 20 Thus, macrophages may also contribute to the phenotypes we observed in our animal models. The interaction and relative contribution of macrophages and AECs to acute lung inflammation remain to be determined.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Stimulation with LPS can induce the expression of iNOS, COX-2, proinflammatory cytokines, and chemokines in microglia/ macrophages [21]. Subsequently, activated microglia/ macrophages may secrete many pro-inflammatory cytokines, including IL-1b and TNF-a, which in turn can act on these cells in an autocrine manner [22].…”
Section: Discussionmentioning
confidence: 99%